The association of social media use and other social factors with symptoms of attention-deficit/hyperactivity disorder in Egyptian university students - Mustafa Mohammed Hassan; Hisham Ahmed Orebi; Basem Salama; Ibrahim Ali Kabbash (BMC Psychiatry)
Abstract Background Attention-Deficit/Hyperactivity Disorder (ADHD) is one of the most common neurodevelopmental disorders of childhood. Many studies reported that excessive social media use is more likely to develop symptoms of ADHD. Methods A cross-sectional study was carried out at Tanta University. The study recruited a total sample of 933 college students from Tanta University from five randomly selected colleges. Data was collected using self-administrated questionnaires made in Google Forms sent to social media groups of students. We used the Adult ADHD Self-Report Scale (ASRS-v1.1) Symptom Checklist instructions. Results The total number of respondents was 933. Those at risk of ADHD represented 30.5%. All sociodemographic variables were not found to significantly affect the risk for ADHD except for the presence of the father in the family. This of ADHD significantly increased to 42.3% and 44.4% for those whose fathers were traveling abroad or separated from their mothers, respectively (p = 0.031). The risk for ADHD significantly decreased among those who practice sports to reach 24.1% compared to 33.8% for those who did not (p = 0.002). The risk for ADHD increased significantly among those who used mass media to watch reels. ADHD risk was found to increase with increased hours of watching media during the study period (p < 0.001) during weekends (p = 0.001) and holidays (p = 0.038). Multivariate analysis showed that practicing sports independently reduces the risk for ADHD (Exp B = 0.679). Meanwhile, both watching reels and hours of using media during the study period independently increase the risk (Exp B = 1.493 and 1.390, respectively). Conclusion There are many factors affecting ADHD, we found that watching reels, status, stories, and shorts and the number of hours spent on social media during the study period are independent risk factors. Practicing sports is an independent protective factor. Most of the factors need further studies.